Association between the prevalence rates of circadian syndrome and testosterone deficiency in US males: data from NHANES (2011–2016) - Xiao, Yunfei; Yin, Shan; Cui, Jianwei; Bai, Yunjin; Yang, Zhenzhen; Wang, Jiahao; Wang, Jia (Frontiers in Nutrition, 2023)
Objective: To explore the association between the prevalence rates of circadian syndrome (CircS) and testosterone deficiency (TD). Materials and Methods: Cross-sectional analysis was conducted on basis of the National Health and Nutrition Examination Survey 2011-2016. The target population was males aged ≥20 years old. Three multivariable logistic regression models were built to elucidate the association between the prevalence rates of CircS and TD. Interactive and stratified analyses were employed to explore whether some variables can modify the above association. Sensitivity analyses were also conducted to verify the stability of the results with extreme values removed. Results: Totally 3,436 eligible participants were involved. Multivariable logistic regression in the fully-adjusted model suggested the CircS group had a significantly higher prevalence rate of TD compared to the non-CircS group (OR=2.284, 95%CI 1.569 to 3.323). No significant correlation between the number of CircS components and TD was observed in any of the three models. The interactive and stratified analyses showed the association was more obvious in the population with moderate or vigorous activities. The results were robust after extreme data were excluded. Conclusion: There is a positive association between the prevalence rates of CircS and TD in U.S. adult males. The association becomes more obvious owing to moderate or vigorous activities.